Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (Institute of Development Studies, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z

Applying Adaptive Management in a Fragile Context – Case Study - Lonsdale, Jane; Green, Duncan; Robertson, Kelly (DT Global, 2023)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523